A non-invasive method to assess the reproductive status of the European badger (Meles meles) from urinary sex-steroid metabolites - Sugianto, NA; Dehnhard, M; Newman, C; Macdonald, DW; Buesching, CD (Elsevier, 2020)
Due to their unique reproductive physiology and behaviour, European badgers (Meles meles) are often used as a model to study mammalian reproduction. For reproductive endocrinology, circulating hormone levels are conventionally measured directly from blood samples. However, routine blood sampling is often not practical for wild animals and may induce stress affecting measurement accuracy. Non-invasive alternatives are thus of interest. Circulating hormones are metabolized through different routes, either by the kidneys, to be excreted through urine, or by the liver, to be excreted through faeces. These metabolites can thus be used as a proxy of hormone measurements, provided the species-specific metabolic characteristics are known. Here we tested the suitability of measuring urinary metabolites of circulating plasma sex-steroid hormones (testosterone in males and oestrogen in females) with enzyme immunoassays to assess the reproductive status of the European badger (Meles meles). Biological validation evidenced that urinary testosterone metabolite (UTM) and urinary total oestrogen metabolite (UEM) excretion patterns both corresponded with seasonal badger reproductive patterns on a population level, signaling correlation over a broad time frame. On an individual level, concurrent sampling of urine and plasma showed that male plasma testosterone and UTM levels correlated significantly across seasons, but no short term correlation was evident for total oestrogen and UEM in females. Thus, in badgers, urinary sex-steroid metabolites can be used reliably in the short term to assess male reproductive status at the individual level, but only at the broader population level for females.